Perancangan Sistem Manajemen Apotek: Integrasi Data Obat dan Penjualan Secara Digital - Tyo, Rahardian Prasetyo; Arisantoso (Journal of Informatics, Electrical and Electronics Engineering, 2025)
The manual management of drug data and sales transactions in pharmacies often leads to several issues, including recording errors, service delays, and difficulties in generating reports. This study aims to design a web-based pharmacy management system that integrates drug inventory and sales data into a single platform to enhance operational efficiency and information accuracy. The system was developed using the Waterfall method, encompassing the stages of requirement analysis, system design, implementation, and testing. The application was built as a web-based system and evaluated using black-box testing to ensure that all features functioned according to the specified requirements. The testing results indicated that the system achieved a transaction recording accuracy rate of 98%, accelerated data entry processes by 65% compared to manual methods, and maintained stability across all test scenarios. These findings suggest that the proposed system effectively improves pharmacy operations by making them more structured, faster, and less error-prone, while contributing to the digitalization of pharmaceutical services.